L-ASPARAGINASE INDUCED CENTRAL VENOUS THROMBOSIS IN ACUTE LYMPHOBLASTIC LEUKEMIA - S, Lavanya; K, Vijayan; Dharamsi, Abhay; A, Rajasekaran; A, Vijayakumar (Indian Journal of Pharmacy Practice)
To report a case of central venous thrombosis following treatment of acute lymphoblastic leukemia with L-asparaginase. A 13-year-old master presented with an acute lymphoblastic leukemia associated with three episodes of focal onset convulsions with secondary generalization, headache and altered sensorium. He was 2 2 initially treated with 5000 u/m of L-asparaginase followed by 10,000 u/m every third day for 4 weeks. After a week’s course of L-Asparaginase, the patient experienced central venous thrombosis. MRI showed thrombosis of the sagittal, transverse and straight sinuses on the right side with partial recanalisation, suggesting a drug induced neurotoxic reaction. According to the Naranjo probability scale, the central venous thrombosis was probably caused by L-Asparaginase. L-Asparaginase-induced central venous thrombosis is rarely reported shortly after beginning L-asparaginase therapy in patientswith acute lymphoblastic leukemia. However, bleeding or thrombosis occurring as a direct result of changes in coagulation factors has not been frequently reported. The purpose is to evaluate the current knowledge of central venous thrombosis in association with ALL in children. Health care professionals should be aware of this potential adverse reaction and monitor the patients regularly during L-asparaginase therapy
Keywords: L-asparaginase; Central Venous Thrombosis; Acute Lymphoblastic Leukemia